Corporate strategy for hospitality - Knowles, Tim. (Burnt Mill, Harlow, Essex : Longman, 1996)
This book contains: The Concept oof Strategic Management; Laying the Groundwork for the Strategic Planning Process; Strategic Management in the Hospitality Industry...
Keywords: Strategic planning; Strategic planning; Hospitality industry; Hotels